PENGARUH SENAM KREASI TERHADAP MOTORIK KASAR PADA ANAK-ANAK UMUR 5-6 TAHUN DI KELURAHAN MESAT SENI - Wawan Syafutra; Ahmad Syahri; Asri Putra Sorita (LP4MK STKIP PGRI Lubuklinggau, 2022)
The purpose of this study was to determine whether there was an influence on children's gross motor development, creative gymnastic methods using a random sampling research design. The population in this study were 10 children at the arts center. The sampling technique was total sampling and the variable in this study was creative gymnastics. Data analysis using t-test statistics. The instruments used in this study were agility, speed and balance test instruments. The mean result of the initial test was 224 and the final test was 238. From the results of the difference test, it was obtained for the experimental group 55.0 that the t-count value was 10,042 with a table value of 2.01 with a significance of 0.00 ≥ 0.05. So it can be concluded that the method of physical exercise is increasing.